PENERAPAN ECOPRINT MENGGUNAKAN TEKNIK POUNDING DALAM EKSPLORASI ETNOMATEMATIKA PADA ASPEK OPTIMASI BIDANG KANVAS DI SDN PULOAMPEL - Pertiwi, Sari Putri; Huda, Miftahul; Sholihin, Badru; Aziz, Fino Kartana; Sopianti, Nadila Aulia; Amrillah, Mu’tasim Bi (LPPM Universitas Bina Bangsa, 2024)
The Students at SDN Puloampel consider the mathematics lessons to be complicated and boring. This is because the mathematics taught in school is different from the mathematics encountered in daily life. Therefore, the application of mathematics is necessary to help students understand its usefulness. Ethnomathematics is one approach that can be utilized to address this issue. Through the ecoprint approach using the pounding technique, it is hoped that the students at SDN Puloampel will gain an understanding of the benefits of mathematics in daily life, especially in geometric patterns. The goal of this activity is to explore the mathematical understanding of SDN Puloampel students through the ethnomathematics approach by conducting ecoprint activities using the pounding technique. The results of this activity show that most students have not yet mastered symmetrical positioning or the optimal placement of objects within a space. However, the students were deemed capable of measuring the provided canvas area. Additionally, the students were found to have a fairly high level of creativity. The ecoprint activity can serve as an opportunity for ethnomathematics activities to help students solve problems in everyday life